EFEK APLIKASI QUIZIZZ TERHADAP MOTIVASI DAN HASIL BELAJAR KOGNITIF SISWA SMP PADA MATERI SISTEM PERNAPASAN MANUSIA - Dianita Rahmayani; Hasan Subekti (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aims to describe students learning motivation preferences and cognitive learning outcomes using Quizizz on the respiratory system material. The participants of this study were class VIII SMP Negeri 1 Pacitan, class VIII F (experimental class), and class VII G (control class). Data collection techniques using motivational questionnaires and giving pretest and posttest. The questionnaire instrument was designed according to the indicators of learning motivation and the tests (pretest and posttest) referred to indicators of cognitive learning outcomes. The statistical test of cognitive learning outcomes between classes VIII F and VIII G also showed consistent results where the average increase test for classes VIII F and VIII G gave the results that there was a difference in the average increase in average between classes VIII F and VIII G with the (p<0.01). The conclusions of this study indicate that the Quizizz evaluation media affects learning motivation and student learning outcomes. This research implies that the teacher can determine interesting and motivating media to be used in science learning so that it can affect student learning outcomes for the better. The use of Quizizz media is very helpful for students in online learning and tends to develop learning motivation during a pandemic and is in line with the Ministry of Education and Culture's policy on education policy in the COVID-19 pandemic.